Penerapan Hermeneutika Dalam Tafsir Pembebasan Asghar Ali Engineer - Walid, Muhammad (ULUL ALBAB Jurnal Studi Islam, 2004)
A tendency to make liberation as paradigm to interpret holy book (al-Qur' an) is the new tendency. That is fonn of unsatisfaction into products of intepretation which is considered no relent ,with contemporary problems. Regarded the products of interpretation have ignored the revolutionary values that hare been being the ultimate mission of revelation. That is the Ali's reason to use hermeneutical approach in interpretating al Qur 'an. According to Ali Indian's conditions has relemncy with al-Qur 'an when revealed. In hermeneutical approach Ali explored the liberation and revolutionary values in the verses of Qur 'an. Ali has concluded that all verses of Qur'an have liberation values for who oppressed like in India.